The specs that matter [and the specs that don't]. - Gladstone, Darren (PC World Philippines)
Technology stores and shopping sites bombard you with details about a device's speeds, resolutions, formats, and more. But much of that data is less important than it may seem. These are the specs to pay attention to when you're in the market for a PC, laptop, HDTV, camera and router.